Understanding the brown planthopper (Nilaparvata lugens Stål) resistance in rice through biological and biochemical responses - Darshana Brahma; S. Rajna; Subhash Chander; C.N. Rajarushi; Ranjith Kumar Ellur; Jessa Joseph (Crop Protection, 2026)

Identification and Characterisation of Super Susceptible Bread Wheat (Triticum aestivum L.) Landraces against Leaf Rust Pathogen (Puccinia triticina Eriks.) - Naman Raj; Ujjwal Kapoor; Ramesh Bhurta; Vrinda Batra; Subhash Bijarania; Niharika Mallick; M. G. Mallikarjuna; Vaibhav Kumar Singh; Atul Kumar; Om Prakash Gangwar; Pramod Prasad; Subhash Chander Bhardwaj; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

Interactive Effects of Elevated CO2, Temperature, and Weed Competition on Mungbean - Dasari Sreekanth; Deepak Vishwanath Pawar; Rajeev Kumar; Shobha Sondhia; P. K. Singh; J. S. Mishra; Ankita Sinha; Subhash Chander; Nagaraju Mukkamula; B. Kiran Kumar (Agricultural Research, 2026)

Canopy orientation influences sunburn fruit temperature and peel anatomy in Kinnow and Daisy mandarins - Subhash Chander; Khushdeep Singh; Krishan Kumar (Vegetos, 2026)

Kaolin and salicylic acid mitigate sunburn and enhance stress-responsive biochemical and fruit quality traits in Daisy Mandarin (Citrus reticulata Blanco) under arid conditions - Khushdeep Singh; Subhash Chander; Shalini Jhanji; Krishan Kumar; Gurteg Singh (Journal of Plant Biochemistry and Biotechnology, 2026)

Virulence analysis and geographical distribution of Puccinia striiformis f. sp. tritici pathotypes in North Western plains zone of India (2019–2021) - Muhammad Rafi Bawari; Ajit Singh; Rajender Singh Beniwal; Keshav Saharan; Om Prakash Gangwar; Pramod Prasad; Subodh Kumar; Subhash Chander Bhardwaj (Indian Phytopathology, 2026)

Graphene-engineered interfaces enable stable, high-efficiency dry-processed ecofriendly flexible perovskite solar cells - Subhash Chander; Inderpreet Kaur (Chemical Engineering Journal, 2026)

One-Pot Biogenic Fabrication of Novel Carbon Embedded Green Mesoporous Magnetite (Fe3O4@MBC) Nanocomposite from Mango-Leaf Biowaste: An Economical and Recyclable Nanoadsorbent for Improved Sequestration of Toxic Metal Ions from Synthetic and Electroplating Wastewater - Subhash Chander; Asha Gupta (Water, Air, & Soil Pollution, 2026)

ABO3-based perovskite oxides for gas sensors: A review of recent advancement in materials, mechanisms, and strategies for real-time applications - Subhash Chander; S.K. Tripathi; Inderpreet Kaur (Chemical Engineering Journal, 2025)

Biology, demographic traits and predation rate of Cheilomenes sexmaculata (Fabricius) (Coleoptera: Coccinellidae) on peach leaf curl aphid, Brachycaudus helichrysi (Kaltenbach) (Hemiptera: Aphididae) - Aryan Bhandari; Chander Singh; Subhash Chander Verma; Prem Lal Sharma; Vishav Gaurav Singh Chandel; Rajeshwar Singh Chandel; Anshuman Semwal; Sushmita; Simran Sharma (Phytoparasitica, 2025)

Exploring FabH inhibitors for antimicrobial therapy: medicinal chemistry, synthetic approaches, and SAR evaluation - Rajiv Patel; Gurpreet Singh; Kumari Kajal; Nandini; Perwez Alam; Harsha Kharkwal; Subhash Chander (Molecular Diversity, 2025)

Biology and life tables of the predatory mite (Neoseiulus longispinosus) on different developmental stages of the two-spotted spider mite (Tetranychus urticae) on carnation (Dianthus caryophyllus) cultivars - Pankaj Sharma; Vishav Gaurav Singh Chandel; Subhash Chander Verma; Prem Lal Sharma; Rajeshwar Singh Chandel; Nikita Chauhan; Chander Singh; Anshuman Semwal; Aryan Bhandari; Sushmita Goel; Simran Sharma; Shashank Kaundal (Experimental and Applied Acarology, 2025)

Effect of temperature and host plants on fitness traits and demographic parameters of Thrips parvispinus (Karny) (Thripidae: Thysanoptera) - Vaddi Sridhar; Kerur Vishwanath Raghavendra; Kurubarahalli Bhoothanna Ramesh; M. Kumaraswamy Sunil; Subhash Chander (Crop Protection, 2025)

Biological attributes and population growth parameters of five dominant syrphids against Brevicoryne brassicae infesting cabbage - Shivani Palial; Subhash Chander Verma; Prem Lal Sharma; Nikita Chauhan; Chander Singh (Phytoparasitica, 2025)

Functional response of temperature tolerant and control strain of Aenasius arizonensis against different densities of Phenacoccus solenopsis Tinsley - Kirankumar G N; Sachin S. Suroshe; Chaitanya M; K. Srinivas; Keerthi M C; Subhash Chander (Phytoparasitica, 2025)

Influence of coloured shade nets on shoot and root growth of dragon fruit stem cuttings - Ajaypartap Singh; Subhash Chander; J. S. Brar (Vegetos, 2025)

Correction: Performance Evaluation of INSAT‑3D Derived Outgoing Long Wave Radiation Over India Using Remotely Sensed Observations - Anoop Kumar Mishra; Chander Singh Tomar; Gajendra Kumar; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2025)

Brassinosteroids: Unveiling Their Role in Fruit Ripening and Quality - Omkar Warang; Panchaal Bhattacharjee; Sajal Debbarma; Subhash Chander (Applied Fruit Science, 2025)

Management of Tetranychus urticae Koch (Acari: Tetranychidae) on cucumber using Blaptostethus pallescens poppius (Hemiptera: Anthocoridae) and Neoseiulus longispinosus (Evans) (Acari: Phytoseiidae) under polyhouse conditions - Subhash Chander Verma; Prem Lal Sharma; Vishav Gaurav Singh Chandel; Rajeshwar Singh Chandel; Nidhi Sharma; Priyanka Sharma; Nikita Chauhan; Chander Singh (International Journal of Tropical Insect Science, 2025)

Trans situ conservation of Piper nigrum L. in India—a review - Doddamalur Appaji Deepak; Gudihalli Muninarayanappa Puneeth; Ravi Gowthami; Muthusamy Shankar; Subhash Chander; Era Vaidya Malhotra; Sunil Archak; Anuradha Agrawal (Genetic Resources and Crop Evolution, 2025)

Performance Evaluation of INSAT-3D Derived Outgoing Long Wave Radiation Over India Using Remotely Sensed Observations - Anoop Kumar Mishra; Chander Singh Tomar; Gajendra Kumar; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2025)

“Effect of total phenol on the control of leafminer ( Phytomyza horticola ) infestation in Pea plants” - Gunjali Dengta; Tanuja Banshtu; Subhash Chander Verma; Neha Gautam; Priyanka Sharma (Natural Product Research, 2024)

Impact of Different Tillage and Residue Retention Practices on Soil Nutrients, Microbial Community Composition and Grain Yield of Malt Barley - Om Parkash Ahlawat; Anil Khippal; Karnam Venkatesh; Rajender Singh Chhokar; Subhash Chander Gill; Prem Lal Kashyap; Ajit Singh Kharub; Lokendra Kumar; Neeraj Kumar; Anu Sharma; Kamini Kumari; Sonia Sheoran; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Soil carbon sequestration potential of different land use systems: evidence from sub-humid southern plains and Aravalli hills of Rajasthan, India - Ram Bhawan Meena; Subhash Chander Meena; Avinash Chandra Rathore; Dinesh Chand Meena; Roshan Lal Meena; Nurnabi Meherul Alam; Kamal Kishor Sharma; Prabhat Kumar; Gopal Lal Meena; Murli Dhar Meena (Environmental Monitoring and Assessment, 2024)

The impact of varying glucosinolate and phenolic levels in different genotypes of cauliflower on the larval population of Pieris brassicae - Tanuja Banshtu; Siddhant Thakur; Subhash Chander Verma; Gunjali Dengta; Neha Gautam; Sapna Katna (International Journal of Tropical Insect Science, 2024)

Unraveling the enigma of root-knot nematodes: from origins to advanced management strategies in agriculture - Sumit Vashisth; Pankaj Kumar; Vishav Gaurav Singh Chandel; Rakesh Kumar; Subhash Chander Verma; Rajeshwar Singh Chandel (Planta, 2024)

Correction to: On the Changes in Precipitation Spectrum Over India Using High-Resolution Precipitation Estimates from Remote Sensing Observations - Anoop Kumar Mishra; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2024)

Pyroxasulfone based tank-mix herbicide combinations for diverse weed flora control in wheat - Shiv Ram Samota; Rajender Singh Chhokar; Dharam Bir Yadav; Nitesh Kumar; Subhash Chander Gill; Harohalli Masthigowda Mamrutha (Crop Protection, 2024)

Potential of yellow sticky trap apropos monitoring and mass trapping of insect pests of tomato (Lycopersicon esculentum Miller): a field study - Kerur Vishwanath Raghavendra; Balodi Rekha; Kurubarahalli Bhoothanna Ramesh; Kannan Thomas Felix; Subhash Chander (International Journal of Tropical Insect Science, 2024)

Feeding potential and foraging behaviour of cheilomenes sexmaculata (F.) on cotton whitefly, Bemisia tabaci (Gennadius) - Rakesh Kumar; Sachin S. Suroshe; Y. Venkanna; M. C. Keerthi; Anoop Kumar; Subhash Chander (International Journal of Tropical Insect Science, 2024)

Efficient Water Management Tactics for Mitigating Fruit Crop Diseases - Pradeep Kumar Vishwakarma; Subhash Chander; P. K. Nimbolkar (Applied Fruit Science, 2024)

Practical approaches to enhance water productivity at the farm level in Asia: A review - Raj Pal Meena; Venkatesh Karnam; Hullehally Thimmappa Sujatha; Subhash Chander Tripathi; Gyanendra Singh (Irrigation and Drainage, 2024)
The global population is constantly increasing, reached 8 billion in November 2022 and is expected to reach 9 billion by 2037. This increased population is expected to increase the demand for food, clothing and shelter, which in turn are heavily dependent on limited water resources. The available freshwater resources for agricultural use are further declining due to overexploitation and changing climate in the major food baskets of the world. This increasing water scarcity is exacerbated by expanding cities due to increasing urbanization. This calls for a new look at the allocation of water to agriculture. Therefore, the development of new strategies to improve agricultural water use may serve as an important adaptation strategy. This review attempts to include a comprehensive review of the literature on (i) the status and definition of water productivity and (ii) factors responsible for low water productivity (WP) in Asian agriculture. Furthermore, it contains practical approaches to enhance water use efficiency at the farm level covering all field crops and a range of soil types, which include (i) agronomic interventions; (ii) genetic interventions, such as the identification and cultivation of crop cultivars with high WP; and (iii) genotype, environment and crop management interactions for higher WP.

Biology and functional response of Oenopia sauzeti (Mulsant) on peach leaf curl aphid, Brachycaudus helichrysi (Kaltenbach) - Nikita Chauhan; Chander Singh; Subhash Chander Verma; Prem Lal Sharma; Rajeshwar Singh Chandel; Vishav Gaurav Singh Chandel; Vibhuti Sharma; Anshuman Semwal; Lalit Kalia (Phytoparasitica, 2024)

Enhancing Wheat Productivity Through Genotypes and Growth Regulators Application Under Higher Fertility Conditions in Sub-humid Climate - Rajender Singh Chhokar; Neeraj Kumar; Subhash Chander Gill; Subhash Chandra Tripathi; Gyanendra Singh (International Journal of Plant Production, 2024)

Wheat as a new host for potato aphid Macrosiphum euphorbiae Thomas (Hemiptera: Aphididae) and construction of its age-stage two-sex life tables - Y. N. Venkatesh; S. Rajna; Sachin S. Suroshe; Sunil Joshi; Subhash Chander (Cereal Research Communications, 2024)

Defoliator attack (Diorhabda lusca maulik) on Kharik (Celtis australis L.): effect on nutritive value, phenology and biomass productivity - Vaishali Sharma; D. R. Bhardwaj; Dhirender Kumar; Prashant Sharma; Subhash Chander Verma; Rohit Bishist (Agroforestry Systems, 2024)

On the Changes in Precipitation Spectrum Over India Using High-Resolution Precipitation Estimates from Remote Sensing Observations - Anoop Kumar Mishra; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2024)

Unlocking the Potential of Metaxenia in Fruit Crop Enhancement: A Comprehensive Review - Nandkishor M. Kanade; Subhash Chander; P. K. Nimbolkar (Applied Fruit Science, 2024)

Entropy generation and exergy loss of R123-MWCNTs nanorefrigerant in flow condensation - Ravinder Kumar; Dwesh K Singh; Subhash Chander (International Journal of Refrigeration, 2024)

Sustaining Rice-Wheat System Through Integrated Nutrient Management via FYM or Sesbania Aculeata in India on Long Term Basis - Subhash Chander; S C. Tripathi; Karnam Venkatesh; R. P. Meena; Neeraj Kumar; R. S. Chhokar; Nitesh Kumar; Shiv Ram Samota; Deepa Sharma; Gyanendra Singh (International Journal of Plant Production, 2023)

Spatial distribution and optimum sample size for monitoring of water lily aphid Rhopalosiphum nymphaeae (L.) in Makhana Euryale ferox Salisb - Vinod K. Padala; N Ramya; Manoj Kumar; S Rajna; Mandla Rajashekhar; YN Venkatesh; SM Raut; Subhash Chander; IS Singh; Mohd. Monobrullah (International Journal of Tropical Insect Science, 2023)

Sequestration of Ni (II), Pb (II), and Zn (II) utilizing biogenic synthesized Fe3O4/CLPC NCs and modified Fe3O4/CLPC@CS NCs: Process optimization, simulation modeling, and feasibility study - Subhash Chander; Sangita Yadav; Asha Gupta; Neha Luhach (Environmental Science and Pollution Research, 2023)

Experimental study on flow condensation pressure drop of R123-MWCNTs nanorefrigerant - Ravinder Kumar; Dwesh K Singh; Subhash Chander (International Journal of Refrigeration, 2023)

Imazethapyr-Resistant Jungle Rice (Echinochloa colona) in Soybean Growing Belt of Central India: A Case Study - Subhash Chander; Dibakar Ghosh; Vikas C. Tyagi; C. R. Chethan; Deepak Pawar; Yogita Gharde; Bhumesh Kumar; P. K. Singh (Agricultural Research, 2023)

Sustainability Assessment of Rice-Wheat System Through Organic Fertilizers and Green Manuring in Sub-Tropical Humid Climate - Subhash Chander; S. C. Tripathi; Karnam Venkatesh; Neeraj Kumar; R. P. Meena; R. S. Chhokar; Nidhi Kamboj; Nitesh Kumar (International Journal of Plant Production, 2023)

Mapping the risk of quarantine pest Sternochetus mangiferae under different climate change scenarios through species distribution modelling - Gundappa Baradevanal; Subhash Chander; Hari Shankar Singh; Doddanagouda Srinivasa Reddy; Shailendra Rajan (International Journal of Tropical Insect Science, 2023)

Genetic diversity analysis of severely infesting invasive thrips, Thrips parvispinus (Karny) in chilli (Capsicum annuum L.) in India - Kerur Vishwanath Raghavendra; Kurubarahalli Bhoothanna Ramesh; Rajan Remani Rachana; Chowdanayak Mahendra; Surender Kumar Singh; Subhash Chander (Phytoparasitica, 2023)

Biology and life table of Diaeretiella rapae against Brevicoryne brassicae on different cultivars of cauliflower - Shikha Thakur; Subhash Chander Verma; Prem Lal Sharma; Rajeshwar Singh Chandel; Priyanka Sharma; Shubham Sharma; Prajjwal Sharma (Phytoparasitica, 2023)

Deciphering host plant resistance mechanisms of rice genotypes resistant against Brown Planthopper - Prabhulinga Tenguri; Subhash Chander; Ranjith K. Ellur; P. S. Arya; Yogesh Yele (Euphytica, 2023)

Mirid bug Nesidiocoris tenuis (Reuter), a potential challenge to bottle gourd Lagenaria siceraria (Molina) Standley production: a study from India - Kerur Vishwanath Raghavendra; Naresh Manohar Meshram; Kurubarahalli Bhoothanna Ramesh; Mogili Ramaiah; Kannan Thomas Felix; Visvash Vaibhav; Balodi Rekha; Hans Raj Sardana; Subhash Chander (Phytoparasitica, 2022)

Using diffusion of innovation framework with attitudinal factor to predict the future of mobility in the Indian market - Subhash Chander Arora; Megha Sharma; Vinod Kumar Singh (Environmental Science and Pollution Research, 2022)

Wheat spike blast: genetic interventions for effective management - Hanif Khan; Shabir Hussain Wani; Subhash Chander Bhardwaj; Kirti Rani; Santosh Kumar Bishnoi; Gyanendra Pratap Singh (Molecular Biology Reports, 2022)

Functional response and predatory potential of coccinellid predator, Oenopia kirbyi Mulsant (Coccinellidae:Coleoptera) on rose aphid, Macrosiphum rosae L. (Aphididae: Hemiptera) - Mahesh Balaso Gaikwad; Subhash Chander Verma; Prem Lal Sharma; Rajeshwar Singh Chandel; Nalini Challa; Panma Yankit; Santosh C. Kedar (International Journal of Tropical Insect Science, 2022)

Characterization of five new pathotypes of Puccinia triticina identified from Northeast India, Nepal, and Bangladesh - Subodh Kumar; Subhash Chander Bhardwaj; Om Prakash Gangwar; Pramod Prasad; Ranjana Chakrabarty; Prem Lal Kashyap; Hanif Khan; Siddanna Savadi; Baidya Nath Mahato; Paritosh Kumar Malaker (Australasian Plant Pathology, 2022)

An intelligent epilepsy seizure detection system using adaptive mode decomposition of EEG signals - Gulshan Kumar; Subhash Chander; Ahmad Almadhor (Physical and Engineering Sciences in Medicine, 2022)

Interactions of six spotted ladybird beetle, Cheilomenes sexmaculata (F.) with its host Phenacoccus solenopsis Tinsley and Intraguild members - Geethu S.; Sachin S. Suroshe; Subhash Chander; Venkanna Y. (International Journal of Tropical Insect Science, 2022)

Feeding potential and foraging behaviour of Cheilomenes sexmaculata (F.) on the cotton aphid, Aphis gossypii glover - Y. Venkanna; Sachin S. Suroshe; Subhash Chander; Sweetee Kumari (International Journal of Tropical Insect Science, 2021)

ESOPA: a GUI-based MATLAB platform for estimation of earthquake spectral source parameters, inelastic attenuation, high-frequency decay kappa, and fmax-model - Rohtash Kumar; Raghav Singh; Subhash Chander Gupta; Amritansh Rai; Prashant Singh; Aquib Ali; Arjun Kumar; Satya Prakash Maurya (Arabian Journal of Geosciences, 2021)

Conservational Tillage and Weed Management Practices Enhance Farmers Income and System Productivity of Rice–Wheat Cropping System in Central India - Dibakar Ghosh; C. R. Chethan; Subhash Chander; Bhumesh Kumar; R. P. Dubey; H. S. Bisen; S. K. Parey; P. K. Singh (Agricultural Research, 2021)

Assessing the risk of mango quarantine pest Deanolis sublimbalis Snellen under different climate change scenarios - Gundappa Baradevanal; Subhash Chander; P. D. Kamala Jayanthi; H. S. Singh; D. Srinivasa Reddy (Journal of Plant Diseases and Protection, 2021)

Biology, predatory potential and functional response of Mallada desjardinsi (Navas) on melon aphid, Aphis gossypii glover - Deeksha Kumari; Subhash Chander Verma; Prem Lal Sharma; Mahesh Balaso Gaikwad (International Journal of Tropical Insect Science, 2021)

Characterization of three new Yr9-virulences and identification of sources of resistance among recently developed Indian bread wheat germplasm - Om Prakash Gangwar; Subodh Kumar; Subhash Chander Bhardwaj; Prem Lal Kashyap; Pramod Prasad; Hanif Khan (Journal of Plant Pathology, 2019)

Virulence and molecular analysis of atypical pathotypes of yellow rust pathogen in India - Om Prakash Gangwar; Subodh Kumar; Prem Lal Kashyap; Subhash Chander Bhardwaj; Pramod Prasad; Siddanna Savadi; Hanif Khan; Deepshikha (Indian Phytopathology, 2019)

Stage-specific reprogramming of defense responsive genes during Lr24-mediated leaf rust resistance in wheat - Pramod Prasad; Siddanna Savadi; Subhash Chander Bhardwaj; Prem Lal Kashyap; Om Prakash Gangwar; Hanif Khan; Subodh Kumar; Ravinder Kumar; Virupaksh Patil (Journal of Plant Pathology, 2019)

Impact of Elevated CO2 and Temperature on Brown Planthopper Population in Rice Ecosystem - G. Guru Pirasanna Pandi; Subhash Chander; Madan Pal Singh; Himanshu Pathak (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Analysis of spatial distribution of genetic diversity and validation of Indian foxtail millet core collection - Subhash Chander; K. V. Bhat; Ratna Kumari; Sanjay Sen; A. B. Gaikwad; M. V. C. Gowda; N. Dikshit (Physiology and Molecular Biology of Plants, 2017)

Development of a Forewarning Model to Predict Rice Leaf Folder (Cnaphalocrocis medinalis Guenee) Incidence in Punjab, India - Preetinder Singh; Subhash Chander; Mazhar Husain; Vishwa Pal; Parminder Singh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Effect of Sowing Date and Cultivars on Aphid Infestation in Wheat with Climate Change Adaptation Perspective - Subhash Chander; Mazhar Husain; Vishwa Pal; Himanshu Pathak; S. D. Singh; Ramesh Harit; Vinod Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Effect of azimuthal coverage of an earthquake on moment tensor solutions estimated by waveform inversion - Rohtash Kumar; Subhash Chander Gupta; Arjun Kumar (Arabian Journal of Geosciences, 2015)

Simulation of climatic change impact on crop-pest interactions: a case study of rice pink stem borer Sesamia inferens (Walker) - Selvaraj Krishnan; Subhash Chander (Climatic Change, 2015)

Determination of Thermal Constant and Development Threshold of Pink Borer, Sesamia inferens Walker - K. Selvaraj; Subhash Chander; N. R. Prasannakumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Structure-based virtual screening and docking studies for the identification of novel inhibitors against wild and drug resistance strains of HIV-1 RT - Subhash Chander; Ashok Penta; Sankaranarayanan Murugesan (Medicinal Chemistry Research, 2015)

In-silico design and study of novel piperazinyl β-carbolines as inhibitor of HIV-1 reverse transcriptase - Penta Ashok; Hardik Sharma; Hiren Lathiya; Subhash Chander; Sankaranarayanan Murugesan (Medicinal Chemistry Research, 2015)

Population structure and association mapping studies for important agronomic traits in soybean - BHUPENDER KUMAR; AKSHAY TALUKDAR; INDU BALA; KHUSHBU VERMA; SANJAY KUMAR LAL; RAMESH LAL SAPRA; B. NAMITA; SUBHASH CHANDER; RESHU TIWARI (Journal of Genetics, 2014)

Antioxidants from defatted Indian Mustard (Brassica Juncea) protect biomolecules against in vitro oxidation - Anita Dua; Subhash Chander; Sharad Agrawal; Ritu Mahajan (Physiology and Molecular Biology of Plants, 2014)

De novo design and in-silico studies of novel 1-phenyl-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole-3-carboxylic acid derivatives as HIV-1 reverse transcriptase inhibitors - Ashok Penta; Subhash Chander; S. Ganguly; S. Murugesan (Medicinal Chemistry Research, 2014)

Characterization of brown planthopper damage on rice crops through hyperspectral remote sensing under field conditions - N. R. Prasannakumar; Subhash Chander; R. N. Sahoo (Phytoparasitica, 2014)

Simulation of rice brown planthopper, Nilaparvata lugens (Stal.) population and crop-pest interactions to assess climate change impact - M. Sujithra; Subhash Chander (Climatic Change, 2013)

Synthesis, characterization, and pharmacological evaluation of benzothiopyran derivatives as a novel class of calcium channel blockers - Rajkumari Nalwaya; Arvind Sahai; Subhash Chander; Manish Sharma; Ruchi Malik; Gaurav Sarsodia (Medicinal Chemistry Research, 2013)

Silibinin Exerts Sustained Growth Suppressive Effect against Human Colon Carcinoma SW480 Xenograft by Targeting Multiple Signaling Molecules - Balaiya Velmurugan; Subhash Chander Gangar; Manjinder Kaur; Alpna Tyagi; Gagan Deep; Rajesh Agarwal (Pharmaceutical Research, 2010)

Identification of QTL for maize resistance to common smut by using recombinant inbred lines developed from the Chinese hybrid Yuyu22 - Jun-qiang Ding; Xiao-ming Wang; Subhash Chander; Jian-sheng Li (Journal of Applied Genetics, 2008)

Using molecular markers to identify two major loci controlling carotenoid contents in maize grain - Subhash Chander; Y. Q. Guo; X. H. Yang; J. Zhang; X. Q. Lu; J. B. Yan; T. M. Song; T. R. Rocheford; J. S. Li (Theoretical and Applied Genetics, 2008)

ATRA promotes alpha tocopherol succinate-induced apoptosis in freshly isolated leukemic cells from chronic myeloid leukemic patients - Surender Kumar; Krishan Lal Khanduja; Neelam Verma; Subhash C. Verma; Pramod Kumar Avti; Chander Mohan Pathak (Molecular and Cellular Biochemistry, 2007)

Residue Evaluation of Controlled-Release Formulations of Imidacloprid Against Rice Leaf Folder - B. Ram Prasad; Vidya S. Singh; Subhash Chander; Jitendra Kumar (Bulletin of Environmental Contamination and Toxicology, 2007)

Inhibitory effects of Azadirachta indica on DMBA-induced skin carcinogenesis in Balb/c mice - Ashwani Koul; Nupur Mukherjee; Subhash Chander Gangar (Molecular and Cellular Biochemistry, 2006)